Characterization and Fine Mapping of a Rice Leaf‐Rolling Mutant Deficient in Commissural Veins. Issue 5 (10th August 2017) - Jing, Wen; Cao, Chengjuan; Shen, Like; Zhang, Hongsheng; Jing, Guangqin; Zhang, Wenhua
Abstract : Leaf shape is an important target trait for rice ( Oryza sativa L.) ideal plant‐type breeding. To understand the molecular mechanism controlling leaf shape, we identified a leaf‐rolling mutant from a 'Nipponbare' mutant bank irradiated with γ‐ray. This mutant exhibited rolled and yellow‐striped leaves, a delayed heading date, and decreased plant height and grain yield. A histological analysis showed that the mutant was deficient in forming the commissural vein (CV) in leaves and was thus designated as commissural vein deficient 1 ( cvd1 ). Genetic analysis revealed that the cvd1 phenotype was controlled by a single recessive gene. The CVD1 gene was fine mapped to a 66.9‐kb interval between the markers IM29941 and IM30008 on chromosome 3. Sequencing analysis revealed that only a deletion of two nucleotides in the BEL1‐like homeodomain protein gene (Os03g0732100) within the candidate region of CVD1, resulting in a frameshift mutation and predicted truncation of protein product. These results will be useful to clone the CVD1 gene and understand the molecular mechanisms regulating CV formation and leaf development.